2009
DOI: 10.1186/1757-7241-17-35
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion in the critically ill: does storage age matter?

Abstract: Morphologic and biochemical changes occur during red cell storage prior to product expiry, and these changes may hinder erythrocyte viability and function following transfusion. Despite a relatively large body of literature detailing the metabolic and structural deterioration that occurs during red cell storage, evidence for a significant detrimental clinical effect related to the transfusion of older blood is relatively less conclusive, limited primarily to observations in retrospective studies. Nonetheless, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 30 publications
1
73
1
1
Order By: Relevance
“…14 In the trauma patient population, we identified 4 singlecentre retrospective studies examining the impact of storage lesion using a cutoff of 14 days to denote old blood. While studies have varied in their inclusion criteria, particularly the number of units transfused, there is a trend toward studies reporting an increase in adverse patient outcomes following transfusion of older blood, including multiorgan failure, 26 longer ICU/hospital length of stay, 27 pneumonia 44 and other major infections 17,45 and all-cause mortality. 30,[32][33][34] Trauma patients who receive large volumes of blood as part of massive transfusion protocols may have an increased risk of death compared with those who receive smaller total volumes of old blood, suggesting that a dose effect of older blood may exist for various outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…14 In the trauma patient population, we identified 4 singlecentre retrospective studies examining the impact of storage lesion using a cutoff of 14 days to denote old blood. While studies have varied in their inclusion criteria, particularly the number of units transfused, there is a trend toward studies reporting an increase in adverse patient outcomes following transfusion of older blood, including multiorgan failure, 26 longer ICU/hospital length of stay, 27 pneumonia 44 and other major infections 17,45 and all-cause mortality. 30,[32][33][34] Trauma patients who receive large volumes of blood as part of massive transfusion protocols may have an increased risk of death compared with those who receive smaller total volumes of old blood, suggesting that a dose effect of older blood may exist for various outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of these changes is controversial, with no consensus regarding a cut-off for fresh or old RBCs. An increase in infection rates and morbidity following transfusion of old blood has been described [2,3,4,5,6,7,8,9,10,11]. Other groups did not find a correlation between the storage time of transfused RBCs and patient outcome [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 98%
“…These investigations have assessed post-transfusion differences in clinical outcomes not only in adults but also in the pediatric population. Studies have reported an increase in morbidity and mortality upon transfusing older stored RBCs in situations such as acute trauma requiring large volumes of transfused blood, cardiovascular surgery, adult critical care, and pediatric medicine (Gorman et al, 2008;Nee et al, 2010;Gauvin et al, 2010;Vandromme et al, 2009).…”
mentioning
confidence: 99%
“…Previous publications have shown the benefits in providing a metabolic substrate to maintain ATP (Zimrin & Hess, 2009;Wang et al, 2012) and DPG levels during the storage (Dawson et al, 1981a(Dawson et al, , 1981bSt. Cyr, Ericson, & Johnson, 2010, 2014. Taking a metabolic supplementation for at least 5 days could benefit subsequent blood donations.…”
mentioning
confidence: 99%